﻿Protective effect of lacosamide and topiramate treatment against Pentylenetetrazole-induced kindling and associated cognitive dysfunction in rats - Michaela Shishmanova-Doseva (Pensoft Publishers, 2022)
Cognitive impairment is considered the most common comorbidity in epilepsy. The aim of the present study was to explore the effects of long-term treatment with lacosamide and topiramate on epileptogenesis and related cognitive dysfunction in an experimental model of pentylenetetrazole (PTZ)-induced kindling. The latter was induced by the repeated administration of subconvulsive dose of PTZ (40 mg/kg, s.c.) on every alternate day for 8-9 weeks. Both drugs were applied daily in a dose of 10 mg/kg p.o. 30 min before PTZ injection. To assess behavioral comorbidities all rats underwent one active and one passive avoidance tests. The results show that lacosamide significantly suppressed the progression of kindling, while the effect of topiramate was not so pronounced on seizure development. Long-term treatment with both antiepileptic drugs managed to ameliorate the kindling-associated impairment of learning and memory. Lacosamide and topiramate improved active and passive learning abilities and facilitated the formation of short- and long-term memory traces. Both drugs failed to prevent the hyperactivity associated with epilepsy.